2019
DOI: 10.3390/su11216059
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Environmental, Social, and Personal Factors on the Usage of the App “Environment Info Push”

Abstract: This study analyzed citizens' willingness to use the Environmental Info Push app to participate in air quality control and air pollution prevention. The participants used the app for two weeks and then we investigated the users' opinions about factors relevant to the app, air pollution control, and prevention. Answer sheets to questionnaires were received from 347 participants. All of them were valid and the study conducted research simulation and statistical analysis with SPSS 19 Statistics software and Smart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Xu and Ou [78] indicated that awareness of the environment is vital for low-carbon behavior. Recent research conducted by Liao et al [79] supported this result; their study finding revealed that environmental factors such as CC influenced individual willingness to control air pollution in society. Deepening organizational CSR and implementing green initiatives and practices have emerged as critical strategic mechanisms affecting the globe and individual livelihoods [80].…”
Section: Discussionmentioning
confidence: 74%
“…Xu and Ou [78] indicated that awareness of the environment is vital for low-carbon behavior. Recent research conducted by Liao et al [79] supported this result; their study finding revealed that environmental factors such as CC influenced individual willingness to control air pollution in society. Deepening organizational CSR and implementing green initiatives and practices have emerged as critical strategic mechanisms affecting the globe and individual livelihoods [80].…”
Section: Discussionmentioning
confidence: 74%
“…Further, they largely reported that only way to reduce exposure is to change jobs, which they do not perceive as a real option given their limited levels of education and skill. This feeling of having no alternatives may also further reduce their willingness to perceive the risks of air pollution and take averting action [28]. Further, there was no mention of receiving any support from local authorities or non-government stakeholders in dealing with air pollution exposure.…”
Section: Explaining the Limited Averting Behaviours And Responsesmentioning
confidence: 99%
“…We used the Aerocet-831 (Met One Instrument, Inc.) for PM exposure and the microAeth, AE51 (AethLabs, CA) to measure black carbon (BC) [26,27]. More details of these instruments and measurements can be found in (28).…”
Section: Measurements Of Ambient Pm25 and Personal Exposurementioning
confidence: 99%
“…Liao et al. (2019) explored the use of a sociological application termed “environment info push” to examine anthropological threats and concluded that individual willingness to control and prevent air pollution is critical. Padula et al.…”
Section: Introductionmentioning
confidence: 99%
“…Grover and Singh (2014) estimated kitchen wastes like plastics and metals and established positive correlation with family size. Liao et al (2019) explored the use of a sociological application termed "environment info push" to examine anthropological threats and concluded that individual willingness to control and prevent air pollution is critical. Padula et al (2018) also studied environmental pollution and social factors as contributors to premature birth in Fresno County in California and concluded that multiple pollution exposures with increased risk for untimely birth was higher among the most disadvantaged population.…”
Section: Introductionmentioning
confidence: 99%